Diet of invertebrates sampled in leaf-bags incubated in a tropical headwater stream - Carvalho, Emerson M. de (2009)
The diet of macroinvertebrates sampled in leaf-bags incubated in a tropical stream was analyzed on a spatial scale (one forested and one deforested area) and on a temporal scale (dry and rainy seasons). The macroinvertebrates were mostly represented by detritivores specialized in fine detritus (69%), followed by generalist detritivores (10% with a diet based on fine and coarse detritus), carnivores (10%), omnivores (8%), and one detritivore genera specialized on coarse detritus (3%). The detritivores exhibited a broad spatial and temporal distribution and were represented mainly by Ephemeroptera, Trichoptera and Diptera. Phylloicus sp. (Trichoptera) consumed mostly coarse detritus (CPOM) and can be classified as the unique specialist shredder in this stream. Carnivores were represented by Anacroneuria sp. (Plecoptera), Hetaerina sp. and Heteragrion sp. (two Odonata). Omnivory was observed for Anacroneuria sp. and Smicridea sp. (Trichoptera), which evidently varied spatially and temporally in the proportion of the food consumed. The high diversity and the wide distribution of the taxa that used organic matter as food resource demonstrated the great importance of this food item to the macroinvertebrates community in this tropical stream.